2018
DOI: 10.3892/etm.2018.6290
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase C‑α/heme oxygenase‑1 signaling pathway improves mitochondrial dynamics in lipopolysaccharide‑activated NR8383 cells

Abstract: Mitochondrial function and morphology are dynamically regulated by fusion and fission. Heme oxygenase-1 (HO-1), which may be upregulated by protein kinase C-α (PKC-α), improves mitochondrial dynamics by controlling the balance between fusion and fission and. However, whether the PKC-α/HO-1 signaling pathway is one of the underlying mechanisms in adjusting mitochondrial dynamics in lipopolysaccharide (LPS)-activated macrophages has remained elusive. To explore this, NR8383 cells were pre-treated with PKC-α inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Research shows that activation of PKC-a/HO-1 signaling pathway increases SOD activity and diminishes ROS content in LPS-activated alveolar macrophage cells [38]. Thus, the results in this study suggest that HO-1 is upregulated in lung injury and TEAS has a protective effect against I/R injury by possibly upregulating HO-1 expression.…”
Section: Discussionsupporting
confidence: 58%
“…Research shows that activation of PKC-a/HO-1 signaling pathway increases SOD activity and diminishes ROS content in LPS-activated alveolar macrophage cells [38]. Thus, the results in this study suggest that HO-1 is upregulated in lung injury and TEAS has a protective effect against I/R injury by possibly upregulating HO-1 expression.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, SD/H challenge up‐regulated the expression of p‐Drp1 ser616 and down‐regulated Mfn2, indicating SD/H induced mitochondrial fission. Recent studies have documented that HO‐1 plays an essential role in the regulation of mitochondrial fission . Haemin treatment significantly inhibited the ischaemia/reperfusion‐induced up‐regulation of Drp1 expression and enhanced the down‐regulation of Mfn2 in a mouse model of liver injury and thus attenuated hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple isozymes of PKC can be categorized into three groups, including conventional (α, βI, βII, and γ), novel (β, ε, η, and θ), and atypical (ζ and ι) [42]. Among these isoforms, PKCα is one of the most prominent modulators of HO-1 expression, which improve mitochondrial dynamics via increasing the expression of fusion proteins [13]. The effect of PKCα was confirmed by our results indicating that MVS-induced HO-1 expression was mediated through PKCα membrane translocation and phosphorylation, which were inhibited by Gö6983 or transfection with its siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C (PKC)α is a member of the classical PKCs that takes a part in the regulation of cellular functions [12]. Upregulation of HO-1 via activation of PKCα could enhance fusion proteins and ameliorate mitochondrial injury [13]. Our previous report also indicated that rosiglitazone (a PPARγ agonist) increases HO-1 expression through the PKCα signaling pathway in HPAEpiCs [6].…”
Section: Introductionmentioning
confidence: 99%